Electrohydrodynamic preparation of particles, capsules and bubbles for biomedical engineering applications - Enayati, Marjan; Chang, Ming-Wei; Bragman, Felix; Edirisinghe, Mohan; Stride, Eleanor (Colloids and surfaces. A, Physicochemical and engineering aspects, 2011)
[Display omitted] ▶ Electrohydrodynamic (EHD) processing has become a highly active area of research. ▶ It is a highly versatile method for preparing structures at the micro and nano scales. ▶ We review the physical principles and its past, present and future applications. Electrohydrodynamic (EHD) processing is a method of generating liquid droplets through the application of a large electrical potential difference. It has a wide range of applications in both industrial processes and analytical instrumentation. Research carried out over the last decade has greatly increased the capabilities of EHD processing, providing the capability to coat, print, spin, thread, bubble or encapsulate a wide variety of materials. One of the reasons interest in EHD processing has escalated in recent years is due to its ability to prepare structures at the micro and nano scales. This review paper focuses on the biomedical applications of the various products, especially in drug delivery, and considers the latest achievements in micro- and nano-carrier production. A brief description of the basic physical principles underlying the process is provided and the range of experimental configurations, from single to multi-needle coaxial processing, is examined, together with the resulting structures. Finally the applications of EHD processing and its products are considered, demonstrating its potential, not only for particle and fibre formation, but as a powerful technique for the encapsulation of bioactive materials such as proteins, enzymes, antibiotics and DNA fragments in polymeric particles.